One year of high-intensity interval training improves exercise capacity, but not left ventricular function in stable heart transplant recipients: A randomised controlled trial. (February 2014) - Rustad, Lene A; Nytrøen, Kari; Amundsen, Brage H; Gullestad, Lars; Aakhus, Svend
Background: Heart transplant recipients have lower exercise capacity and impaired cardiac function compared with the normal population. High-intensity interval training (HIIT) improves exercise capacity and cardiac function in patients with heart failure and hypertension, but the effect on cardiac function in stable heart transplant recipients is not known. Thus, we investigated whether HIIT improved cardiac function and exercise capacity in stable heart transplant recipients by use of comprehensive rest- and exercise-echocardiography and cardiopulmonary exercise testing. Design and methods: Fifty-two clinically stable heart transplant recipients were randomised either to HIIT (4 × 4 minutes at 85–95% of peak heart rate three times per week for eight weeks) or to control. Three such eight-week periods were distributed throughout one year. Echocardiography (rest and submaximal exercise) and cardiopulmonary exercise testing were performed at baseline and follow-up. Results: One year of HIIT increased VO 2peak from 27.7 ± 5.5 at baseline to 30.9 ± 5.0 ml/kg/min at follow-up, while the control group remained unchanged (28.5 ± 7.0 vs. 28.0 ± 6.7 ml/kg per min, p  < 0.001 for difference between the groups). Systolic and diastolic left ventricular functions at rest and during exercise were generally unchanged by HIIT. Conclusions: Whereas HIIT is feasible in heart transplant recipients and effectively improves exercise capacity, it does not alter cardiac systolic and diastolic function significantly. Thus, the observed augmentation in exercise capacity is best explained by extra-cardiac adaptive mechanisms.